Online excursions at the restaurant as a modern active learning method - Mostova, L. M.; Zaparenko, G. V. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses the possibility of the use of online excursions as an effective means of organizing students’ academic and experimental activity under the conditions of e-learning environment. The background of the use of online excursions in the teaching and learning process of the specialty 181 «Food Technologies» of the subject area 18 «Production and Technologies» is stated. Advantages and disadvantages of online excursions as a method of active learning are analyzed. A script for an online excursion at the restaurant is developed. Participation in online excursions allows students to make step-by-step acquaintance with the layout design, functions and peculiar features of the premises used for getting and storing products, manufacturing areas (pre-cooking shop, hot and cold dishes shops) as well as features of the management of the amenity space, commercial and technical departments. The use of the online excursions during the educational process gives students the opportunity to learn principles of the organization of the restaurant business, see state-of-the-art equipment and understand conditions of its operation which is crucial for better conceptual learning and development of the necessary competences.